2012
DOI: 10.1124/jpet.112.194803
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal and Chemical Regulation of Paraoxonases in Mice

Abstract: In humans and rodents, paraoxonase (PON/Pon) 1 expression and activity in livers and serum are higher in females than in males, and some drugs increase paraoxonase's expression. However, the underlining mechanisms of gender-divergent expression and chemical regulation of Pon1 remain largely unknown. The present study determined the regulatory mechanisms contributing to gender-divergent and chemically altered Pon expression in mouse livers. Pon1 mRNA was much more abundant in the livers of mice than other tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 59 publications
3
21
2
1
Order By: Relevance
“…For Pons, the present study has shown that both Pon2 and 3 mRNAs are lower in the jejunum and ileum than in the large intestine, in contrast to the previous report of similar levels (Cheng and Klaassen, 2012). For Akrs, the mRNAs of Akr1a1/1a4, 1b3, 1c12, 1c13, 1c19, and 1e1 in certain tissue(s) in the present study are not fully consistent with a previous report (Pratt-Hyatt et al, 2013).…”
Section: Discussioncontrasting
confidence: 57%
“…For Pons, the present study has shown that both Pon2 and 3 mRNAs are lower in the jejunum and ileum than in the large intestine, in contrast to the previous report of similar levels (Cheng and Klaassen, 2012). For Akrs, the mRNAs of Akr1a1/1a4, 1b3, 1c12, 1c13, 1c19, and 1e1 in certain tissue(s) in the present study are not fully consistent with a previous report (Pratt-Hyatt et al, 2013).…”
Section: Discussioncontrasting
confidence: 57%
“…Unfortunately, non-human primate liver samples were not available for analysis, and the persistence of expression patterns between species for PON2 in the liver is unclear. Previous studies had examined the developmental expression of PON1 mRNA in liver and of paraoxonase activity in plasma of mice, and found PON1 levels to increase with age [3537], in agreement with the present findings. PON3 temporal expression has received less attention, with limited studies showing a decrease or an increase with age [3739].…”
Section: Discussionsupporting
confidence: 92%
“…If tested separately in each sex, this gene-SNP pair is an eQTL in males (P-value = 5.5 × 10 −3 ) but not females (P-value = 5.0 × 10 −1 ). Interestingly, PON2 does not exhibit sex-specific gene expression (P-value = 6.3 × 10 −1 , FDR 89.2%) but has been associated with sex-specific effects in oxidative stress responses (Cheng and Klaassen 2012;Giordano et al 2013;Polonikov et al 2014). …”
Section: −3mentioning
confidence: 99%